Association between leukemic immunophenotype and overall survival in patients with acute promyelocytic leukemia: a retrospective cohort study - Zha, Xuan; Ma, Li; Yue, Yun; Wei, XiaoYu; Sun, Baolan; Wang, Weiguo (Frontiers in Cell and Developmental Biology, 2026)
IntroductionAcute promyelocytic leukemia (APL) is a distinct subtype of acute myeloid leukemia (AML) with unique clinical features. Flow cytometry (FCM) immunophenotyping analysis is crucial for accurate diagnosis and prognostic stratification. This study aims to explore the association between specific immune phenotype markers in APL patients and overall survival (OS).MethodsIn this retrospective cohort study, immunophenotypic data from 72 APL patients were analyzed by FCM. Continuous and categorical variables are presented as mean ± standard deviation and frequency (percentage), respectively. Group comparisons were performed using ANOVA and Chi-square tests. Cox proportional hazards models were used to identify prognostic factors for OS, with results expressed as hazard ratios (HRs) and 95% confidence intervals (CIs). Kaplan-Meier survival analysis was employed to assess the impact of CD56, CD2, CD34, and CD200 expression on OS. Subgroup analyses were conducted based on age, gender, white blood cell count (WBC), and disseminated intravascular coagulation (DIC).ResultsThe baseline age (p = 0.513) and gender (p = 0.881) were comparable across different PML-RARα isoform groups. Compared to non-APL AML, APL blasts were characterized by significantly higher expression of CD33, CD13, CD9, and MPO (all p < 0.05), and lower expression of CD7, CD34, CD56, CD38, CD200, and HLA-DR (all p < 0.001). The PML-RARα (S-type) group showed relatively higher expression of CD34, CD2, and CD200 than the L-type group. Univariate Cox analysis revealed that expression of CD34, CD2, CD56, and CD200 were all significantly associated with poorer OS. After multivariate adjustment, CD2 (adjusted HR = 1.04, 95% CI: 1.01–1.07, p = 0.004) and CD200 (adjusted HR = 1.04, 95% CI: 1.01–1.06, p = 0.009) remained independent adverse prognostic factors. Subgroup analysis confirmed that the negative prognostic impact of CD2 and CD200 expression was consistent across different patient subgroups.ConclusionCompared with non-APL-AML patients, APL patients (PML-RARα (S-type) and PML-RARα (L-type)) exhibit unique immunophenotypic changes. The expression frequencies of CD56, CD2, CD34, and CD200 in leukemia cells are significantly correlated with the OS of APL patients, and the high expression of these indicators before treatment may be an adverse prognostic factor for APL patients.